Sovershenstvovanie tehniki dvizhenij i special'noj tehnicheskoj podgotovki kak osnova vysshih dostizhenij v sovremennoj sportivnoj gimnastike - Gaverdovsky, Y. (Science in Olympic Sport, 2019)
Objective. To create an idea of the improvement of the technique of movements and special technical preparation on the basis of the laws of construction of gymnastic movements. Results. In a review article, artistic gymnastics is considered as a specific sports event that differs significantly from others. The technique is analyzed as a subject of mastering, by which is meant biomechanically determined way of solving the motor task chosen by the performer. Possibilities of practical realization of program gymnastic movement from the point of view of accounting for fundamentally important factors are described: mechanism of movement; method and style of performance; motion energy; anatomical and morphological factor of technique; age and gender factor of gymnastic technique; aesthetics of movements; artificial and natural factors of technique; rationality of motion as a generic characteristic. The problem of technical literacy of the coach is highlighted. The importance of improving movements based on objective physical and physiological regularities is emphasized. The structure of gymnastic movements, cause-and-effect relationships (physical factors of gymnast's movement, natural and complex movements, etc.) are analyzed. The issue of early specialization of athletes, implementation of the tendency for early rejuvenation of sports gymnastics was raised. In solving this problem one of the main means that allows to maintain the efficiency of the gymnast for a longer time, his active life in sport is full technical preparation, higher culture of mastering gymnastic exercises. Conclusion. Improvement of the technique of movements and special technical fitness, based on the stated regularities of gymnastic movements` construction is the basis of higher achievements in modern artistic gymnastics.